Prices, availability, and affordability of national essential medicines in public primary hospitals: A cross‐sectional survey in poverty‐stricken rural areas in China. (17th November 2019) - Xu, Rixiang; Li, Shuting; Lv, Xiongwen; Xie, Xuefeng
Summary: Introduction: This study aimed to determine the prices, availability, and affordability of national essential medicines in public primary hospitals in poverty‐stricken areas of Anhui province, China. Methods: A cross‐sectional study was conducted in 143 public primary hospitals in Anhui province, eastern China. Data on access to 44 essential medicines was evaluated using the standardized methodology available in the World Health Organization and Health Action International manual. Results: Median price rates show that 46.51% (21 of 44) of the lowest price generics and 100% of the originator brands were more expensive than the international reference price. The median availability of the 44 medicines was 31.47%, and 65.91% (29 of 44) of the medicines had less than 50% availability. The majority of the medicines were affordable as they would cost less than a day's income in sample areas. Suppliers could respond to 88.27% of the procuring orders raised by the 143 hospitals in the study, but this ranged from 43.96% to 99.86%. Conclusions: There is poor availability and non‐ideal response rate of medicine delivery in public primary hospitals in poverty‐stricken areas in eastern China. Further implementation of national essential medicine policy needs to focus on improving both availability and distribution efficiency in these areas.